2021
DOI: 10.1089/ten.tea.2020.0265
|View full text |Cite
|
Sign up to set email alerts
|

Dental Pulp Cell Sheets Enhance Facial Nerve Regeneration via Local Neurotrophic Factor Delivery

Abstract: An effective strategy for sustained neurotrophic factor (NTF) delivery to sites of peripheral nerve injury (PNI) would accelerate healing and enhance functional recovery, addressing the major clinical challenges associated with the current standard of care. In this study, scaffold-free cell sheets were generated using human dental pulp stem/progenitor cells, that endogenously express high levels of NTFs, for use as bioactive NTF delivery systems. Additionally, the effect of fibroblast growth factor 2 (FGF2) on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(31 citation statements)
references
References 52 publications
2
21
0
Order By: Relevance
“…DPSC sheets act as an NTF transmission system to promote axon extension and significantly enhance nerve regeneration. All these results suggest the optimistic outlook of DPSC sheets for the treatment of peripheral nerve injury [ 40 ]. Currently, new biomaterials, such as nerve conduits and porous scaffolds, are widely used in the treatment of peripheral nerve injury and spinal cord injury.…”
Section: Dpsc Sheets Applicationsmentioning
confidence: 99%
“…DPSC sheets act as an NTF transmission system to promote axon extension and significantly enhance nerve regeneration. All these results suggest the optimistic outlook of DPSC sheets for the treatment of peripheral nerve injury [ 40 ]. Currently, new biomaterials, such as nerve conduits and porous scaffolds, are widely used in the treatment of peripheral nerve injury and spinal cord injury.…”
Section: Dpsc Sheets Applicationsmentioning
confidence: 99%
“…To date, use of DPSC sheets has been reported for the regenerative treatment of a variety of injuries, including but not limited to dental pulp diseases[ 112 ], periodontal tissue diseases[ 121 ], bone defects[ 122 ], nerve injuries[ 123 , 124 ], etc ., and all of these applications have achieved significant results. In one representative clinical study, autologous DPSC sheets from deciduous teeth were transplanted into injured young permanent teeth due to trauma.…”
Section: Derivatives Of Dpscsmentioning
confidence: 99%
“…This transplantation was able to regenerate whole dental pulp, increase the length of the root and reduce the width of the apical foramen at 12 mo after treatment[ 125 ]. Furthermore, the evaluation of DPSC sheets in a rat facial nerve crush injury model in vivo established that in comparison to untreated controls, nerves treated with dental pulp cell sheets had greater axon regeneration through the injury site and superior functional recovery as quantitatively assessed by compound muscle action potential measurements, possibly because the DPSC sheets can highly express neurotrophic factor (NTF) and continuously deliver the NTF to sites of peripheral nerve injury[ 123 ]. Moreover, bioengineered teeth using human DPSC aggregates combined with decellularized tooth matrix or avulsed teeth after traumatic dental injuries can regenerate 3D dental pulp and periodontium equipped with vasculature and innervation in both a preclinical pig model and a pilot clinical trial for treating tooth avulsion[ 126 ].…”
Section: Derivatives Of Dpscsmentioning
confidence: 99%
“…In a pilot clinical studies with two patients with periodontal intrabone defects, the same group reported that DPSCs-IPs generated new bones to repair the periodontal defects 9 months after surgical reconstruction (99). For craniofacial nerve regeneration, implantation of DPSCsheets and DPSCs infilled in PLGA artificial nerve conduits significantly promoted crush-injured and segmental defect models of rat facial nerves, respectively (100,101). The superior laryngeal nerve (SLN) plays an essential role in swallowing.…”
Section: Dental Pulp Stem Cells (Dpscs) and Stem Cells From Human Exfoliated Deciduous Teeth (Shed)mentioning
confidence: 99%